(untitled) (Research, Society and Development, 2020)
Adequate quality of estuarine water is necessary for bathing. Thus, it is essential that the community understands the importance of the quality of its estuarine waters, since it directly influences the promotion of the population’s health and well-being. The present study aimed to know the bathing conditions of the estuarine shore of the Ponta do Tubarão State Sustainable Development Reserve through the environmental perception of the residents of the communities of Chico Martins, Barreiras, Diogo Lopes and Sertãozinho, in Macau / RN. 384 interviews were carried out, with the aid of a semi-structured questionnaire with multiple answers, which sought to know the interviewees’ environmental perception regarding bathing. The results obtained affirm that the majority of the residents are male, with low level of education and that the majority fish and live for more than 20 years in their community. Also according to the results obtained, most respondents use the estuary water for fishing or leisure and consider the quality of the water to be good, although it confirms the existence of domestic effluents, the inadequate disposal of solid urban waste and the presence of animals in the estuary area. As a result, it was concluded that the population of the communities surveyed in the Ponta do Tubarão State Sustainable Development Reserve is characterized as follows: despite the high number of sewers, residents say that estuarine water is suitable for consumption.